A coupling model of XFEM/peridynamics for 2D dynamic crack propagation and branching problems. (August 2020) - Liu, Shuo; Fang, Guodong; Liang, Jun; Lv, Dongkai
Highlights: A coupled XFEM and PD is proposed combining with the advantages of XFEM and PD. The coupling model is high accurate to analyze dynamic crack propagation problems. The coupling method exhibits the higher efficiency than the pure PD. Abstract: Peridynamics (PD) and extended finite element method (XFEM) are coupled in the explicit integration scheme to study the 2D dynamic fracture problems. The advantages of PD for the crack propagation and XFEM for the strong displacement discontinuity description of the crack are combined together. The proposed method can improve the computation efficiency in comparison of the pure PD, and can avoid using macroscopic criteria to judge the crack propagation orientation of XFEM. The coupling scheme for the stiffness and mass matrices of PD and XFEM is given in the coupling region. The horizon length δ is examined to study their influences on the convergence of the proposed method. The accuracy of the dynamic fracture simulation using the proposed method is also validated in comparison of experimental and other numerical methods.